PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA APARAT PEMERINTAH DAERAH KABUPATEN MERAUKE - Okto Irianto (Universitas Musamus,Merauke,Papua, 2013)
The purpose of this study was to determine (1) the effect of budget participation on performance of the echelon personnel in the Merauke district government, (2) the influence of leadership style on the performance of officials in the government echelon Merauke district, (3) the influence of organizational culture on performance of the apparatus of the echelon in the Merauke district government and (4) the simultaneous effect of budget participation, leadership style and culture on the performance of the apparatus of the echelon in the Merauke district governmentThe sample was echelon officials in the work unit area (on education) Merauke. The main instrument for data collection was a questionnaire and measured with a Likert scale. Respondents totaled 58 people. The entire questionnaire filled and managed using multiple regression data analysis.The results showed that the partial budget participation, leadership styles, and organizational culture positive and significant impact on the performance of the echelon government Merauke area. Meanwhile, simultaneously budgetary participation, leadership styles, and organizational culture are also positive and significant effect